3 (m - 2) = 2 (3m + 3) Use the Distributive Property on both sides
3m - 6 = 6m + 6 Subtract 6m from both sides
-3m - 6 = 6 Add 6 to both sides
-3m = 12 Divide both sides by -3
m = -4
The equation is
Y=-3/1 +2
Y-Intercept at (0,2)
Answer:
-25 and 2
Step-by-step explanation:
x + y = -23
xy = 50, so y = 50 /x
.
x + 50/x =-23, x^2 +23x - 50 = (x-2)(x+25)
so 2 and -25
Answer:
1/6
Step-by-step explanation:
-3/4 - (-1/2) = - 1/4
-2/3 - 5/6 = - 3/2
-1/4 ÷ -3/2
Answer:
C
Step-by-step explanation:
A models an exponentially increasing function.
B models an exponentially decreasing function.
C models a "bell" curve, similar to the one shown.
D models a "logistic" function, an s-shaped curve that smoothly transitions between two horizontal asymptotes.